Implementasi Pembelajaran Berbasis Proyek QuizWhizzer dalam Meningkatkan Self-Efficacy Mahasiswa - Firdiawan Ekaputra (Medan Resource Center, 2026)
The increasing integration of digital technology into higher education requires prospective teachers to develop strong self-efficacy to effectively engage with technology-enhanced learning environments. This study investigates whether Project-Based Learning (PBL) using QuizWhizzer can improve students’ self-efficacy in the Gamification of Chemistry Learning course. A quantitative approach was employed using a pre-experimental method with a One-Group Pretest–Posttest Design. The participants were Chemistry Education students enrolled in the Gamification of Chemistry Learning course at Universitas Jambi. Data were collected using a self-efficacy questionnaire and analyzed through the Shapiro–Wilk normality test and a paired-sample t-test. The findings revealed that the data were normally distributed and that the paired-sample t-test yielded a significance value of 0.000, indicating a statistically significant improvement in students’ self-efficacy following the implementation of QuizWhizzer-based PBL. These findings demonstrate that integrating authentic project activities with QuizWhizzer effectively strengthens students’ confidence in utilizing educational technology, completing collaborative learning tasks, and solving instructional problems. This study argues that QuizWhizzer-based PBL represents an effective pedagogical strategy for fostering self-efficacy and supporting the development of technology-oriented competencies among prospective chemistry teachers.